If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 5y = -22 Solving -4x + 5y = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -4x + 5y + -5y = -22 + -5y Combine like terms: 5y + -5y = 0 -4x + 0 = -22 + -5y -4x = -22 + -5y Divide each side by '-4'. x = 5.5 + 1.25y Simplifying x = 5.5 + 1.25y
| 7x+6+5x+3=3x-9 | | (9)y-6(y)= | | 56-4x=9-10x | | s/6+3=11 | | 143-4x=6x+13 | | 5(8-3p)=100 | | (8x-3)(2x^2-4x+4)=0 | | x=ay+b | | 5k^2+37k-24=0 | | 9yx-6yx= | | m^2+13m+12=0 | | 9q+1-9= | | 784=16t^2 | | 3(n-8)(3n-4)=0 | | 3-2(x+3)=X-8 | | w(w-5)=24 | | 3f(2)+f(2)*6=36 | | (15+3x)-3x= | | w^2=7w | | 6m+5n=-32 | | 4x-5=12x-45 | | 8x^3+36x^2+40x+12=0 | | 9d=27 | | -7x+9(-4)=-15 | | 56=8(x+3) | | -4+y=20 | | 7=s/2+5 | | (x*x)+(x*x)=2116 | | 10d+6=6d+22 | | X^2+bx+64= | | 122-2x=6x+16 | | 3(t+2)=2-(2t-2) |